The Correlation of Total Percent Fat With Alterations in Cholesterol and Triglycerides in Adults - Sun, Juan; Zhang, Zimu; Liu, Zhen; Li, Jie; Kang, Weiming (Frontiers in Nutrition, 2022)
Background: To evaluate the detailed relationship of total percent fat (TPF) and cardiovascular disease (CVD) related lipid biomarkers among adults and find a non-invasive indicator for screening and monitoring of the high CVD risk population. Methods: Data were from 13160 adults in the National Health and Examination Survey (NHANES) 1999-2018. TPF was assessed by dual-energy x-ray absorptiometry (DXA), and CVD-related lipid biomarkers included total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL) cholesterol, and high-density lipoprotein (HDL) cholesterol. Multivariable linear regression models were used to examine associations of TPF with four kinds of lipid biomarkers, and smooth curve fittings and generalized additive models were used to address the non-linear relationship between them. The inflection points were calculated by the recursive algorithm when non-linearities were detected and then weighted two-piecewise linear regression models were constructed. Results: In multivariable regression, increasing TPF was associated positively with TC, TG, LDL cholesterol, and negatively with HDL cholesterol (all P <0.001). And the non-linear relationships of them were also identified by generalized additive models and smooth curve fittings. When further stratified TPF by sex, the fitted smooth curves were nearly inverted U-shaped and U-shaped, the inflection points were calculated and the weighted two-piecewise linear regression models were constructed, respectively. Conclusions: TPF was significantly associated with CVD-related lipid biomarkers in adults, positively with TC, TG, LDL cholesterol and negatively with HDL cholesterol. It could be used as a non-invasive screener and monitor of high CVD risk population when their TPF were less than the inflection points.